Three-dimensional analysis of nasolabial fold depth as a support for facial reconstruction methods for corpse identification: A literature review - Apriani, Regina Carsa Bagin; Puspitawati, Ria; Gultom, Ferry Pergamus; Soedarsono, Nurtamy; Yuniastuti, Mindya (Science Midwifery, 2024)
Identification of human remains is one of the most important stages in forensic science among the various methods commonly used in the process of identifying unknown human remains. Identification of remains is an issue in both criminal and civil cases. Determining the correct identity of the body is very important in the investigation as a mistake could have fatal consequences. Facial reconstruction is a method that is developing rapidly. The aim of this review is to acknowledge the importance of the nasolabial fold as one of the parameters required for identification using facial reconstruction methods. The depth of soft tissue is important in facial reconstruction. Aging of the face is associated with loss of soft tissue support in the nasolabial sulcus. The nasolabial sulcus is made up of both soft and hard tissue. The depth of the nasolabial sulcus can affect facial expression. 3D computerized facial reconstruction has been developed for a long time, but still requires continuous development using approaches to reconstruct the face. The nasolabial sulcus influences facial expression in facial reconstruction. Technological advances improve or facilitate the work of forensic odontologists, anthropologists, and dentists compared to traditional methods.